2022
DOI: 10.3390/diagnostics12040916
|View full text |Cite
|
Sign up to set email alerts
|

Association of Non-Alcoholic Fatty Liver Disease and Hepatic Fibrosis with Epicardial Adipose Tissue Volume and Atrial Deformation Mechanics in a Large Asian Population Free from Clinical Heart Failure

Abstract: Non-alcoholic fatty liver disease (NAFLD) and cardiovascular disease share several cardiometabolic risk factors. Excessive visceral fat can manifest as ectopic fat depots over vital organs, such as the heart and liver. This study assessed the associations of NAFLD and liver fibrosis with cardiac structural and functional disturbances. We assessed 2161 participants using ultrasound, and categorized them as per the NAFLD Fibrosis Score into three groups: (1) non-fatty liver; (2) fatty liver with low fibrosis sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…From the initial search, 2619 studies were identified. Ultimately, 38 of them were included in the systematic review [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Furthermore, 31 of them were found eligible for meta-analysis ( Figure 1 ), since 7 of the studies included in the systematic review did not have the required quantitative data.…”
Section: Resultsmentioning
confidence: 99%
“…From the initial search, 2619 studies were identified. Ultimately, 38 of them were included in the systematic review [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Furthermore, 31 of them were found eligible for meta-analysis ( Figure 1 ), since 7 of the studies included in the systematic review did not have the required quantitative data.…”
Section: Resultsmentioning
confidence: 99%
“…For example, exercise testing and coronary calcium scoring can help identify ischemic heart disease, N-terminal pro-b-type natriuretic peptide measurements and cardiac ultrasound can help identify HF, cardiac CT is useful to diagnosing valve diseases, and Holter monitoring can detect atrial fibrillation [85]. Useful NITs to diagnose and monitor CV disease are shown in Table 3 [61,[85][86][87][88].…”
Section: Cardiac Endpoints To Include In Hepatic Trialsmentioning
confidence: 99%
“…can complicate accurate and timely diagnosis of HF. Lai et al found that non-alcoholic fatty liver disease without HF is associated with left ventricular diastolic dysfunction and subclinical changes in left atrial contractility [8]. Adamska-Welnicka et al reviewed the difficulty associated with proper HF diagnosis when comorbidities of chronic kidney disease or pulmonary hypertension are present [9].…”
mentioning
confidence: 99%